The Influence of Islamic Financial Literacy, Trust, and Risk Perception on Retail Sukuk Investment Decisions among Muslim Investors in Indonesia - Aziz, Noor; Nevia, Yayah Ikhda; Listanti, Maya (Westscience Press, 2026)
This study investigates the influence of Sharia financial literacy, trust, and risk perception on retail sukuk investment decisions among Muslim investors in Indonesia. Employing a quantitative research design, primary data were collected from 150 respondents using structured questionnaires measured on a Likert scale. The data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results reveal that Sharia financial literacy and trust have a positive and significant effect on retail sukuk investment decisions, while risk perception has a negative and significant effect. Among the variables, trust is identified as the most influential factor in shaping investment behavior. Simultaneously, all independent variables significantly affect investment decisions, with a coefficient of determination (R²) of 0.564, indicating that 56.4% of the variation in investment decisions is explained by the model. These findings highlight the importance of improving Islamic financial literacy, strengthening institutional trust, and managing perceived risks to enhance participation in retail sukuk investments. This study contributes to the growing literature on Islamic finance by providing empirical insights into behavioral determinants of investment decisions in a developing country context.